Square plate with clamped edges under normal pressure producing large deflections - Levy, Samuel (Technical note (United States. National Advisory Committee for Aeronautics), 1942)
A theoretical analysis is given for the stresses and deflections of a square plate with clamped edges under normal pressure producing large deflections. Values of the bending stress and membrane stress at the center of the plate and at the midpoint of the edge are given for center deflections up to 1.9 times the plate thickness. The shape of the deflected surface is given for low pressures and for the highest pressure considered. Convergence of solution is considered and it is estimated that the possible error is less than 2 percent. --